Suspected melanoma only when the lesion is greater than 6mm may harm patients - de Oliveira, Renato Santos (Einstein (Sao Paulo), 2015)
OBJECTIVE: To analyze the distribution of larger diameter in the pathological report of cutaneous melanoma patients. METHODS: Data were obtained from patients seen from 1994 to 2015. Date, sex, age, maximum diameter, histological subtype, primary site, microscopic thickness, mitoses, ulceration, vertical growth phase, and regression were the variables studied. This study was approved by the National Ethics Committee - Brazil Platform. Patients were grouped into smaller diameter (≤6mm) and larger diameter (>6mm). The statistical analysis used the χ(2) test (p<0.05). RESULTS: Of the 292 patients analyzed, 123 were seen between 1994 and 2004, and 169 between 2005 and 2015; in that, 151 women and 141 men, mean age of 52 years. The diameters ranged from 2 to 76mm (mean of 14mm), 81 patients with smaller diameter (≤6mm) and 211 with larger diameter (>6mm). Out of 81 patients with smaller diameter, 29 had invasive melanoma, while 179 of the 211 with larger diameter were invasive. A difference was observed in frequency of vertical growth phase. CONCLUSION: Pigmented skin lesions with diameter smaller than 6mm should not be an excluding factor for biopsies, especially when patients present risk of developing skin cancer.